Rapid Multiplex Testing for Upper Respiratory Pathogens in the Emergency Department: A Randomized Controlled Trial. (5th November 2019) - May, Larissa; Tatro, Grant; Poltavskiy, Eduard; Mooso, Benjamin; Hon, Simson; Bang, Heejung; Polage, Christopher
Abstract: Background: Acute upper respiratory tract infections are a common cause of emergency department (ED) visits and often result in unnecessary antibiotic treatment. Methods: We conducted a randomized clinical trial to evaluate the impact of a rapid, multipathogen respiratory panel (RP) test vs usual care (control). Patients were eligible if they were ≥12 months old, had symptoms of upper respiratory infection or influenza-like illness, and were not on antibiotics. The primary outcome was antibiotic prescription; secondary outcomes included antiviral prescription, disposition, and length of stay (ClinicalTrials.gov# NCT02957136). Results: Of 191 patients enrolled, 93 (49%) received RP testing; 98 (51%) received usual care. Fifty-three (57%) RP and 7 (7%) control patients had a virus detected and reported during the ED visit ( P = .0001). Twenty (22%) RP patients and 33 (34%) usual care patients received antibiotics during the ED visit (–12%; 95% confidence interval, –25% to 0.4%; P = .06/0.08); 9 RP patients received antibiotics despite having a virus detected. The magnitude of antibiotic reduction was greater in children (–19%) vs adults (–9%, post hoc analysis). There was no difference in antiviral use, length of stay, or disposition. Conclusions: Rapid RP testing was associated with a trend toward decreased antibiotic use, suggesting a potential benefit from more rapid viral tests in the ED. Future studies should determine if specific groups are more likely to benefit from testing and evaluate the relative cost and effectiveness of broad testing, focused testing, and a combined diagnostic and antimicrobial stewardship approach.